2008
DOI: 10.1039/b703111d
|View full text |Cite
|
Sign up to set email alerts
|

The complex refractive index of atmospheric and model humic-like substances (HULIS) retrieved by a cavity ring down aerosol spectrometer (CRD-AS)

Abstract: Atmospheric aerosols absorb and reflect solar radiation causing surface cooling and heating of the atmosphere. The interaction between aerosols and radiation depends on their complex index of refraction, which is related to the particles' chemical composition. The contribution of light absorbing organic compounds, such as HUmic-LIke Substances (HULIS) to aerosol scattering and absorption is among the largest uncertainties in assessing the direct effect of aerosols on climate. Using a Cavity Ring Down Aerosol S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
350
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(378 citation statements)
references
References 51 publications
24
350
2
2
Order By: Relevance
“…CRDS was initially focused on the study of gaseous samples (Brown 2003;Berden and Engeln 2009) due to its high sensitivity and ability to measure absolute extinction. It is increasingly applied to the study of aerosols (Smith and Atkinson 2001;Thompson et al 2002Thompson et al , 2008Strawa et al 2003;Pettersson et al 2004;Moosmüller et al 2005;Strawa et al 2006;Butler et al 2007;Miller and Orr-Ewing 2007;Riziq et al 2007Riziq et al , 2008Rudic et al 2007;Dinar et al 2008). CRDS is able to directly measure the total extinction by the sample of particles contained within the optical cavity; this extinction is the sum of scattering and absorption losses.…”
Section: Cavity Ring-down Spectroscopy and Integrating Nephelometrymentioning
confidence: 99%
See 1 more Smart Citation
“…CRDS was initially focused on the study of gaseous samples (Brown 2003;Berden and Engeln 2009) due to its high sensitivity and ability to measure absolute extinction. It is increasingly applied to the study of aerosols (Smith and Atkinson 2001;Thompson et al 2002Thompson et al , 2008Strawa et al 2003;Pettersson et al 2004;Moosmüller et al 2005;Strawa et al 2006;Butler et al 2007;Miller and Orr-Ewing 2007;Riziq et al 2007Riziq et al , 2008Rudic et al 2007;Dinar et al 2008). CRDS is able to directly measure the total extinction by the sample of particles contained within the optical cavity; this extinction is the sum of scattering and absorption losses.…”
Section: Cavity Ring-down Spectroscopy and Integrating Nephelometrymentioning
confidence: 99%
“…The extinction-minus-scattering technique has been used for airborne ambient measurements , characterization of optical properties of biomass burning aerosols (Riziq et al 2007Rudich et al 2007Rudich et al , 2009, retrieving complex refractive indices of humic-like aerosols (Dinar et al 2008), and determining the SSA of isolated aerosol particles (Butler et al 2007;Miller and Orr-Ewing 2007). Instruments have been developed for SSA and aerosol light absorption measurements that combine aerosol cavity ring-down spectrometers (CRDS) and integrating sphere nephelometers using the same laser beam and sample volume (Smith and Atkinson 2001;Thompson et al 2002Thompson et al , 2008Moosmüller et al 2005;Strawa et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The WSOC might potentially affect the properties that determine the aerosols' ability to act as cloud condensation nuclei (Dinar et al, 2006;Padro et al, 2010). It has been also suggested that the WSOC might contribute to the absorption of solar radiation, and thus atmospheric heating and global climate change (Dinar et al, 2008;Mladenov et al, 2010). Furthermore, the wet deposition fluxes of atmospheric watersoluble organic matter (WSOM) indicate that it may be an important temporal source of OC to surface waters and, thus, playing an important role in the global carbon cycle (Jurado et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many more studies have been subsequently carried out to measure the optical extinction of aerosol particles using CRDS [6][7][8][9][10]. Most of these pervious works were based on using either a pulsed YAG laser, which is relatively bulky and limited to only 355, 532 or 1064 nm laser radiation [12][13][14], or a pulsed tunable dye laser, which is cumbersome and not suitable for field study [15].…”
mentioning
confidence: 99%
“…In particular, in situ measurements of the extinction and other optical parameters of atmospheric aerosols are crucial, and these require real-time, accurate, and sensitive techniques that can detect the ambient aerosols and their rapid temporal and spatial changes. Recent years have seen a rapid rise in the use of cavity ringdown spectroscopy (CRDS), a sensitive and direct optical extinction technique, to determine the optical properties of both laboratory generated and atmospheric ambient aerosols [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%